EFEKTIVITAS PENGELOLAAN SEKOLAH MENENGAH KEJURUAN BERSTATUS BADAN LAYANAN UMUM DAERAH (SMK-BLUD) - Arie Wibowo Khurniawan; Illah Sailah; Pudji Muljono; Bambang Indriyanto; M. Syamsul Maarif (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
It needs efforts to continue improving the quality of SMK-BLUD education from various aspects so that the operational implementation can take place optimally. The purpose of this study is to design a strategy to improve the effectiveness of SMK-BLUD through implementing school governance (SG) and total quality management (TQM) using Interpretive Structural Modeling (ISM) analysis. Data obtained through the Group Disscusion Forum (FGD) with expert experts. The results reveals that the strategic planning modeling for improving the effectiveness of SMK-BLUD management is by focusing on increasing TQM having the greatest driving power then focusing on improving of implementation of SG. This improvement can be done by improving the quality of man by fostering strong and decisive leadership in SMK-BLUDs through providing leadership training and opportunities to play roles as leader, for school principals and the teachers. Keywords: ISM, school governance, SMK-BLUD, TQM